Resolution of Implant-Induced Neurosensory Disturbance: A Procedural Failure. Issue 6 (December 2015) - Bhavsar, Ishita; Khalaf, Mohd; Ferrin, John; Al-Sabbagh, Mohanad
Abstract : Purpose: This case report describes the improvement of a patient's neurosensory symptoms after the removal of a mandibular implant within 24 hours of initial placement. After 1 year, neurosensory symptoms resolved, and a different sized dental implant was successfully placed at the same surgical site. Materials and Methods: A 45-year-old woman experienced neurosensory disturbance along the inferior alveolar mandibular nerve after a dental implant surgery. A panoramic radiograph, obtained within 24 hours of implant placement, suggested a possible case of implant intrusion into the inferior alveolar nerve canal. After thorough evaluation, the implant was removed within 24 hours of initial placement, and the patient was followed up for 1 year. The neurosensory functions of the patient's chin and lower lip regions were assessed before implant removal, and 1 month and 1 year after the removal of the implant. Results: Almost complete resolution of altered sensation occurred 1 year after implant removal. A second, shorter implant was placed at the same site with no subsequent symptoms of impaired sensation. Conclusion: This report highlights the plausible placement of a different size dental implant in the same area of previous-implant–induced nerve injury. The authors report that a lack of postoperative radiograph by the surgeon was considered to be a procedural failure.